INHIBITORY POWER OF TOOTHPASTE CONTAINS KENCUR (KAEMPFERIA GALANGA) TO THE GROWTH OF STREPTOCOCCUS MUTANS (SM) BACTERIA - Wahyu Jati Dyah Utami; Rahma Rizki Hutami; Diyah Fatmasari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Dental caries is a disease caused by the interaction between microorganisms, diet, and teeth (host). Streptococcus mutants is most common microorganisms which has a role in the process Microorganisms whose role is Streptococcus mutants. Kencur (Kaempferia galanga) has bactericidal properties because it contains essential oils, flavonoids, polyphenols, and saponins that can inhibit bacterial growth. Aims: The purpose of this study was to determine the ability of kencur extracts 20% in toothpaste to inhibit the growth of Streptococcus mutants. Methods: This was a laboratory experimental research with post-test control group design. The sample was divided into 2 groups, toothpaste without kencur extract as group A and a toothpaste group containing kencur extract. Replication is done 12 times from each group. Incubation was performed for 24 hours at 27 0 C. The results are measured with calipers and the data were analysed by Independent t-test. Results:The results showed that the average of toothpaste A inhibitory zone was 2.95 mm and the toothpaste containing kencur extract was 18.1 mm. Independent test results obtained t-test significant value of 0.000 p<0.05 which means there are differences in the average zone of inhibition significantly between groups kencur extract toothpaste and toothpaste brands A. Conclusion: It can be concluded that, although kencur extracts toothpaste has inhibitory zone against the bacteria Streptococcus mutants however, toothpaste A has a larger inhibition zone.